Sewerage and water-works of St. John's, Newfoundland [electronic resource] - MacDougall, Alan.; Canadian Society of Civil Engineers. ([S.l. : s.n., 1890)
Tables. Caption title. At head of title: Advance proof subject to revision . Canadian Society of Civil Engineers, incorporated 1887, Transactions . "To be read on Thursday, 9th April." Electronic reproduction. Mode of access: Internet. 44